Intestinal Parasite Infection and Its Association with Undernutrition among Early Adolescents in Hawassa University Technology Village, Southern Ethiopia - Amelo Bolka Gujo; Assefa Philipos Kare; Shambel Gussa Shuramo (Advances in Public Health)
Background. Different studies presented negating findings of the association between intestinal parasite infections (IPIs) and undernutrition among early adolescents in Ethiopia. This study was aimed at assessing intestinal parasite infection and its association with undernutrition among early adolescents in four selected districts of the Sidama region. Method. An institution-based cross-sectional study was conducted in October 2020 among 792 early adolescents. The multistage stage sampling was applied to select 16 primary schools. Simple random sampling was applied to select study participants. Trained data collectors administered questionnaires. Stool samples were collected and analyzed. Anthropometric measurements were taken and indices were calculated using AnthroPlus software. Data were entered into and analyzed by SPSS version 25 software. Association between IPI and undernutrition was measured using multivariable analysis. The outputs are presented using an adjusted odds ratio (AOR) with 95% confidence intervals (CIs). Result. The prevalence of IPI, thinness, and stunting was 32% (95% CI: 28.7%, 35.3%), 17.5% (95% CI: 14.8%, 20.2%), and 21.5% (95 CI: 18.6%, 24.4%), respectively. The higher odds of IPIs were observed among adolescents stunted (AOR = 3.61; 95% CI: 2.44–5.33), those who are thin (AOR = 3.07; 95% CI: 2.02–4.66), those who did not wash their hands after toilet (AOR = 1.89; 95% CI: 1.35–2.66), those who ate raw meat (AOR = 1.50; 95% CI: 1.03–2.14), and those whose family did not own toilet (AOR = 1.71; 95% CI: 1.18–2.46). Conclusion. The prevalence of IPI, thinness, and stunting was high and has public health significance in the study area. IPIs were associated with stunting, thinness, lack of toilets, not washing hands after a toilet visit, and eating raw meat. Strengthening nutrition interventions, deworming programs, and health education on personal and environmental hygiene and sanitation are recommended.